Kafaah and Marriage in Jahily and Early Islam (Studies in the History of Islamic Law) - Ahmad Muzakki; Roibin Roibin; Muhammad Muhammad (Universitas Darussalam Gontor, 2024)
Knowing the background to the emergence of a law, the reasons for establishing a sharia law and the history of the formation of the law is an important thing to study.The purpose of this study is to provide readers with an understanding that the application of kafaah in marriage has a long history starting from the Arab Jahiliyah era to the era of the madzhab scholars.This research is in the form of library research, where the tasyri` date books and Islamic history books are the main materials for data exploration. The results of this study indicate thatLineage played a central role in marriage in pre-Islamic Jahiliyya Arab society. In the highly tribal and family-oriented society of Jahiliyya Arab society, lineage was a determinant of social status, protection, political alliances, and inheritance rights.The arrival of the Prophet Muhammad with the religion of Islam brought significant changes in the views of Arab society towards kafaah nasab. Islamic teachings emphasize equality among all human beings before God, thus shifting the focus from nasab as the main factor in marriage to be more inclusive, emphasizing other aspects such as religion and morality. The arrival of the Prophet Muhammad with the religion of Islam brought significant changes in the Arab community’s view of kafaah nasab. Islam still maintains kafaah, but with more humane criteria. Kafaah is a tradition that existed before Islam and was continued by Islam. Islamic teachings emphasize equality among all human beings before God, thus shifting the focus from nasab as the main factor in marriage to be more inclusive, emphasizing other aspects such as religion and morality. Subsequent developments during the time of the ulama’ madzhab kafaah emerged as a logical necessity of the existing legal rules of marriage, balancing the arguments for the benefit of marriage and the principle of egalitarianism in response to the social conditions in each region and the evolving legal logic.